A novel self-assembled hybrid organogel of polypeptide-based block copolymers with inclusion of polypeptide-functionalized graphene. Issue 3 (5th January 2017) - Lei, Wei-Wei; Shi, Ling-Ying; Li, Hang; Li, Chen-Xi; Diao, Yong-Fu; Zhang, Yu-Lin; Ran, Rong
Abstract : Self-assembled hybrid organogels of polypeptide-based BCPs with incorporation of functionalized graphene were generated, and showed enhanced mechanical performance for the potential nanomaterials application. Abstract : Self-assembled hybrid organogels of polypeptides containing block copolymers with the inclusion of polypeptide-functionalized graphene were designed and elaborately prepared, and showed interesting microstructures as well as enhanced mechanical performances. Firstly, a series of peptide-based triblock copolymers (triBCPs), poly(γ-benzyl-l -glutamate)- b -poly-(dimethylsiloxane)- b -poly(γ-benzyl-l -glutamate) (PBLG- b -PDMS- b -PBLG, BDB), with different lengths of PBLG helices, were synthesized and characterized. As the length of the PBLG helices increased, the critical gelation concentration of the BDB triBCPs decreased while the gel–sol transition temperature increased. Moreover, the PBLG covalently modified graphene oxide (GO) sheets were successfully incorporated into the BDB organogels in toluene and hybrid organogels were prepared. In the presence of GO sheets, the minimum gelation concentration of the hybrid organogel was slightly lowered, and the hybrid organogels preserved thermoreversibility. In the hybrid gels, the triBCPs still self-assembled into nanoribbon structures and the functionalized GO sheets were well dispersed in the gel medium, which was obviously observed by transmission electron microscopy. In addition, the inclusion of the functionalized graphene greatly enhanced the mechanical performance of the hybrid gels, which was demonstrated by the significant increase of the moduli and the fracture stress of the hybrid gels compared with the corresponding native gels in the rheology experiments.